Workshop on Medical Ethics - Khurshid Ahmad Nadeem (International Institute of Islamic Thought, 1996)
It was indeed an auspicious occasion when experts in different academic fields came together to discuss questions confronting Muslim society based on recent medical advancements. Many medical doctors, lawyers, and-scholars of Islamic studies met at the International Islamic University, Islamabad, to discuss these matters. Rector Malik Meraj Khalid inaugurated the workshop. The president and prime minister of Pakistan, Farook Ahmad Khan Leghari and Benazir Bhutto, respectively, sent goodwill messages. The legality of organ transplants and autoposies, as well as the exact determination of the actual moment of death, were the main issues of discussion. These issues were analyzed at length in order to determine whether there were substantive differences between the approach(es) of medical specialists and of Islamic studies specialists. Muhammad Tasin, a prominent Pakistani scholar, delivered the keynote address: "The Problem of Corneal Transplantation." He examined the idea of organ transplantation and organ donation after death and found them Islamically permissible. Since the Qur'an and Sunnah contain no clear texts on these questions, he argued that the problem should be resolved through qiyas (analogy). He also argued that, in the case of genuine necessity, the dissection of corpses was lawful and cited a number of authorities to support his opinion. Based on this premise, he declared that corneal transplants were permissible. He also examined critically the arguments of scholars who consider autopsies to be unlawful. Tasin refuted the major argwnent of those opposed to transplantation: Since the individual does not own his/ber body, he/she cannot decide how to dispose of it after death. He cited several Qur'anic verses that describe the individual as the owner of his/ber body and wealth. In general, participants were inclined to support his viewpoint and extend the lawfulness of transplantation to other human organs. They also generally agreed that an organ could be donated lawfully by a living individual if the individual's health would not be affected adversely. The most vehement opposition came from a medical doctor, Rafiq Ahmad Ghuncha (assistant professor of anatomy, Armed Forces Medical College, Rawalpindi). He argued forcefully that a doctor's mandate was confined to the patient's treatment and not to increasing his/her life span. In support, he referred to kidney transplants, which, he said, cost on the aver 284 age about Rs 200,000 (roughly $6,250). In the most successful case, a transplanted kidney scarcely survives for more than four or five years. Moreover, after the operation, a further Rps. 6OOo (roughly $US 200) is required for medication. Eventually, this means that a middle-class family must part with the accumulated resources of virtually all of the patient’s close relatives. In his opinion, moreover, legalizing transplantation would encourage trade in human organs, with the result that poor and exploited segments of society would be lured into donating their organs in the hope of augmenting their income. He quoted several incidents to stress that the legalization of this practice would have disastrous consequences. All participants agreed that trade in human organs was unlawful ...